A survey of intracranial aneurysm treatment practices among United States physicians. (9th February 2017) - Fargen, Kyle M; Soriano-Baron, Hector E; Rushing, Julia T; Mack, William; Mocco, J; Albuquerque, Felipe; Ducruet, Andrew F; Mokin, Maxim; Linfante, Italo; Wolfe, Stacey Q; Wilson, John A; Hirsch, Joshua A
Abstract : Background: Recent surveys have failed to examine cerebrovascular aneurysm treatment practices among US physicians. Objective: To survey physicians who are actively involved in the care of patients with cerebrovascular aneurysms to determine current aneurysm treatment preferences. Methods: A 25-question SurveyMonkey online survey was designed and distributed electronically to members of the Society of NeuroInterventional Surgery, Society of Vascular and Interventional Neurology, and the American Association of Neurological Surgeons/Congress of Neurological Surgeons Combined Cerebrovascular Section. Results: 211 physicians completed the survey. Most respondents recommend endovascular treatment as the first-line management strategy for most ruptured (78%) and unruptured (71%) aneurysms. Thirty-eight per cent of respondents indicate that they routinely treat all patients with subarachnoid hemorrhage regardless of grade. Most physicians use the International Study of Unruptured Intracranial Aneurysms data for counseling patients on natural history risk (80%); a small minority (11%) always or usually recommend treatment of anterior circulation aneurysms of <5 mm. Two-thirds of respondents continue to recommend clipping for most middle cerebral artery aneurysms, while most (51%) recommend flow diversion for wide-necked internal carotid artery aneurysms. Follow-up imaging schedules are highly variable. Neurosurgeons at academic institutions and those practicing longer were more likely to recommend clipping surgery for aneurysms (p<0.05). Conclusions: This survey demonstrates considerable variability in patient selection for intracranial aneurysm treatment, preferred treatment strategies, and follow-up imaging schedules among US physicians.